Lighting in the Performance "Kapai-Kapai" by Arifin C Noer - Puji Koswara (Fakultas Tarbiyah Institut Agama Islam Sunan Giri Ponorogo, 2024)
This article focuses on lighting using GrandMA2 equipment, a lighting designer's work steps, and the lighting arrangement work simulation in the performance "Kapai-Kapai" by Arifin C Noer. This study aims to make lighting designs in theater performances with the script "Kapai-Kapai" by Arifin C Noer. This type of action research uses a qualitative approach, with library research methods, to collect information, theories, and concepts related to lighting in the performing arts, especially theater. Research data sources include books related to performing arts, journal articles, and documents related to the performance "Kapai-Kapai ."Meanwhile, data collection was obtained from observation and interviews. Data analysis is carried out qualitatively. Observational and interview data were analyzed to identify patterns, trends, and findings related to the lighting application in the performance of "Kapai-Kapai ."Modern equipment such as color-adjustable LED lights, special effects with projection, and automatic control allow performances to become even more dynamic and creative. Some lighting designers use computer simulations to plan light effects before the show begins. This allows them to test various scenarios and ensure the lighting matches the artistic vision.